THE INFLUENCE OF MANAGEMENT SUPPORT ON INTERNAL AUDIT EFFECTIVENESS IN SEMI-AUTONOMOUS GOVERNMENT AGENCIES IN THE MINISTRY OF ENVIRONMENT AND FORESTRY IN KENYA - Roselyne, Magero Night; Wamitu, Susan Njeri (European Journal of Business and Strategic Management, 2019)
Purpose: This research paper aimed at investigating the influence of management support on internal audit effectiveness in Semi-Autonomous Government Agencies in the Ministry of Environment and Forestry. Methodology: The study adopted descriptive research design whereby the researcher employed the use of questionnaires for data collection. A sample size of respondents comprising of senior managers, middle level managers, supervisors and audit assistants was considered for this research. The data collected was cleaned and inspected for completeness then coded using SPSS Version 20 software. Descriptive statistics such as the mean and standard deviation were used to describe the data. Further, inferential statistics at 95% level of significance were used. Findings: The findings of the study indicated that the internal audit effectiveness had a positive and significant relationship with the management support. The findings were supported by the literature reviewed in this study. Unique Contribution to Theory, Practice and Policy: The study recommended that development of comprehensive framework to facilitate the recruitment of internal audit staff. Secondly, the study recommends management to provide regular training to internal auditors. Lastly the study recommends management to come up with a policy on the allocation of resources to the internal audit function.